THE ENHANCEMENT OF INFERRING SKILLS AND MASTERY OF CONCEPTS IN CHEMICAL EQUILIBRIUM BY LEARNING CYCLE 3E LEARNING MODEL - pitri yunia; emmawati sofya; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is to describe the effectiveness of  learning cycle 3E  learning model in improving the skills of inference and mastery of concepts in chemical equilibrium material. Learning cycle 3E model is learning through a series of stages (phases of learning) learning phases include: (1) the exploration phase, (2) explanation of the concept phase, and (3) the application of the concept phase. This study used a quasi-experimental method with Non Equivalent (Pretest and Posttest) Control Group Design. Effectiveness of the learning cycle 3E model  is measured by an increase in n-Gain significant. The results showed the average value of n-Gain inference skills for grade control and experimental respectively 0.40 and 0.53, and an average of n-Gain the possession concept for the control and experimental classes respectively 0.44 and 0 , 48. Thus, it can be concluded that the learning cycle 3E learning model in chemical equilibrium material effective to enhance inferensi skill and mastery of concepts in medium categoryKeywords: Learning Cycle 3E, inference skills and mastery of concepts